The resistance to mainstream assumptions about retribution in Job and Tobit as theologically positive deviance - Southwood, K (Transnational Press London, 2022)
This article uses material from organizational studies and medical anthropology and sociology to address the value of the idea that bodily dysfunction or illness depart from a norm of health. It argues that examples of positive deviance can be found in the books of Tobit and in Job. Positive deviance describes behavior that notably departs from expected norms, albeit in a direction that a referent group finds positive. In much of the Hebrew Bible, there is a tight connection between the ideas of wrongdoing, bodily suffering, and retribution. However, the books of Tobit and Job are examples of a departure away from this norm. In Job and Tobit the portrayal of circumstances in the text depart from expected norms with a view to encouraging the referent group (i.e., audiences) towards a positive assessment of the departure. The character Tobit, in line with dominant thought about retribution assumes his blindness is a result of some inadvertent or inherited sinfulness. However, Tobit’s characterisation and dramatic irony prevents audiences agreeing with Tobit’s assessment of circumstances. Similarly, the advice of Job’s friends betrays their assumption that his physical condition must be retribution for wrongdoing. However, Job’s characterisation and dramatic irony prevents audiences agreeing with his friends. More shockingly, the character Yahweh departs from the expected role and becomes a deviant actor. Through resisting simplistic assessments of somatic distress as caused by retribution for wrongdoing, both books are examples of positive deviance that encourage audiences towards more positive norms.